KEBIJAKAN PEMBERIAN KREDIT USAHA RAKYAT (KUR) MIKRO MENURUT INSTRUKSI PRESIDEN NO. 3 TAHUN 2010 TENTANG PROGRAM PEMBANGUNAN YANG BERKEADILAN DALAM PERSPEKTIF UU NO. 10 TAHUN 1998 TENTANG PERUBAHAN ATAS UU NO. 7 TAHUN 1992 TENTANG PERBANKAN - , Fepti Wijayanti, SH; , Haryanto, S.H., MKn. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study is aimed at knowing the concept of the policy in giving the Kredit Usaha Rakyat (KUR) based on the Presidential Instruction Number 3 Year 2010 concerning the Equitable Development Program in the perspective of Law Number 10 Year 1998 concerning the Amendment of Law Number 7 Year 1992 on Banking. This study is the combination of the normative and empirical study. The instruments of the research are the library research and the field research. The library research was conducted by collecting the books, scientific works, and the national laws which are associated with the research variable, whereas the field research was conducted to get the data directly by interviewing. The data analysis was done by using the qualitative approach and the inductive method. The finding of the research reveals that the provision policy of Micro KUR based on the Presidential Instruction Number 3 Year 2010 concerning the Equitable Development Program in the perspective of Law Number 10 Year 1998 concerning the amendment of Law Number 7 Year 1992 on Banking basically do not break the rules or best practice banking because the financing scheme is designed with the credit guarantee. The Micro KUR is heavily promoted as a loan without collateral or the loan that is guaranteed by the government. The KUR agencies define it to the people as the unsecured credit, thus briefly the Presidential Instruction Number 3 Year 2010 as a basic rule of KUR is contrary to the Banking Act.